Evaluation of different water content measurement methods to analyze soil water dynamics - Ventrella D.; Castellini M.; Di Giacomo E.; Giglio L.; Campi P.; Palumbo A.D.; Mastrorilli M. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
In the framework of AQUATER Project (Decision support systems to manage water resources at irrigation district level in Southern Italy using remote sensing information), the main objective of this study has been to monitor the SWC dynamics in a tomato (Foggia) and watermelon (Castellaneta - TA) field cultivations, both located in Southern Italy, by using: (1) the Diviner 2000 (Sentek Pty. Ltd., South Australia), (2) the TDR-100 (Campbell Sci. Shepshed, UK), (3) ThetaProbe Soil Moisture Sensor-ML2x (Delta-T Devices Ltd) and (4) the typical gravimetric methods. The TDR probes were installed horizontally and vertically below the plant row and between crop rows. SWC has been continuously monitored and stored every hour into a CR10X. Moreover, for both the experiments, the SWC was also measured at two different depth (0-20 and 20-40 cm) with the typical thermo-gravimetric method. The soil water dynamic was accurately individuated with the TDR methodology, while the DIVINER allowed to characterize the plant water uptake along the soil profile. However, accurate measurements of surface SWC were obtained by using the Thetaprobe sensor.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)